Bone Mineral Density, Mechanical, Microstructural Properties and Mineral Content of the Femur in Growing Rats Fed with Cactus Opuntia ficus indica (L.) Mill. (Cactaceae) Cladodes as Calcium Source in Diet - Hernández-Becerra, Ezequiel (Nutrients, 2017)
Mechanical, microstructural properties, mineral content and bone mineral density (BMD) of the femur were evaluated in growing rats fed with Opuntia ficus indica (L.) Mill. (Cactaceae) cladodes at different maturity stages as calcium source. Male weanling rats were fed with cladodes at early maturity stage (25 and 60 days of age, belonging to groups N-60 and N-200, respectively) and cladodes at late maturity stage (100 and 135 days of age, belonging to groups N-400 and N-600, respectively) for 6 weeks. Additionally, a control group fed with calcium carbonate as calcium source was included for comparative purposes. All diets were fitted to the same calcium content (5 g/kg diet). The failure load of femurs was significantly lower (p ≤ 0.05) in groups N-60 and N-200 in comparison to N-400, N-600 and control groups. The cortical width (Ct.Wi) and trabecular thickness (Tb.Th) of the femurs in control and N-600 groups were significantly higher (p ≤ 0.05) than Ct.Wi and Tb.Th of femurs in groups N-60 and N-200. Trabecular separation of the femurs in N-60 and N-200 groups showed the highest values compared with all experimental groups. The highest calcium content in the femurs were observed in control, N-600 and N-400 groups; whereas the lowest phosphorus content in the bones were detected in N-200, N-600 and N-400 groups. Finally, the BMD in all experimental groups increased with age; nevertheless, the highest values were observed in N-600 and control groups during pubertal and adolescence stages. The results derived from this research demonstrate, for the first time, that the calcium found in Opuntia ficus indica cladodes is actually bioavailable and capable of improving mineral density and mechanical and microstructural properties of the bones. These findings suggest that the consumption of cladodes at late maturity stage within the diet might have a beneficial impact on bone health.